Do environmental provisions in preferential trade agreements reduce emissions traded in global value chains? - Maisha Fairuz; Neil Foster-McGregor (Asian Development Bank (ADB), 2024)
While global value chains (GVCs) are considered an important development escalator, concerns over their environmental consequences have been increasing. By providing opportunities to shift production to developing economies, GVCs risk carbon leakage. Preferential trade agreements (PTAs) have proved important drivers of GVC trade. In this paper we examine whether the presence and breadth of PTAs is associated with increased emissions embodied in GVC trade, and further ask whether the presence of environmental provisions in PTAs impacts upon emissions traded in GVCs. Our results suggest that the presence of a PTA between partners is associated with increased emissions embodied in GVC trade, with this effect largely the result of increased GVC trade between PTA partners. We also show, however, that the presence of an environmental provision in PTAs can mitigate this effect, with environmental provisions reducing both the scale of GVC trade and the emissions intensity of that trade.
Keywords: F13; F18; Q56; 330; global value chains; CO2 emissions; preferential trade agreements; gravity model